Memory game for hearing impaired students - Cho, Hui Ling (Universiti Malaysia Sarawak (UNIMAS), 2015)
Nowadays, computer becomes an important device in our daily life. Everyone knows how to use a computer. Currently, memon game application can be easilv, found in market. However, hearing impaired students can't. fully enjoy the benefit. The reason being why this circumstance is existed because mostly the memory game application that found in marketplace are not special/v designed. for hearing impaired students. In this project, a memory game application is purpose/- created, for hearing impaired students in order to attract them to play and help them to improve their brain memory. In this game application, sign language cards are adopted to make use of this application and to make sure that the application is interesting enough to attract the attention of hearing impaired students to play it. In addition, the picture of sign language that used in this game application is simple so that hearing impaired students are able to understand clear/, with the , flol4' of the game. Moreover, colorful picture is used to display and as a background to make the overall graphic become more interesting, In order to make sure that the game application is , fulfilled with the user requirement, testing phase, interview and evaluation are being conducted with 15 hearing impaired students from Sekolah Kebangsaan Khas (P), Kota Samarahan. Based on the feedback, majority of the selected students are satisfied with the prototype and enjoyed the memon' game application.